Fractal Dimension and lacunarity based microscopic image texture characterization of coated and non-coated metallic substrates. Issue 2 (3rd April 2022) - Parbat, Debanjan; Bhattacharjee, Uttaran; Paria, Suman; Das, Nilotpal; Chakraborty, Monisha
ABSTRACT: The degree of surface roughness as measured using Fractal Dimension and Lacunarity can serve as quality measures of the coating process. The smoothness of the surface before and after coating is an important characteristic frequently used in surface engineering, to obtain well-polished and smoothened surface finish. We have used Brass plates and coated it with Nickel using electroless and electroplating methods. The images of the coated surfaces were taken using an optical microscope before and after coating. Fractal Dimension (FD) and Lacunarity (λ) of the surface image before and after coating is calculated for comparison using Differential Box-Counting algorithm. Electro-cleaning of the samples in an alkaline degreasing solution is done. Electroplating is carried out in respective electrolytic bath under constant current and temperature conditions. Electroless coating is carried out with a separate Nickel bath at constant temperature of 85° C. The experimental data was validated, which revealed that FD and λ values decreased after coating in all the cases. The lower value of FD and λ after coating suggests more regularity in the surface patterns or smoothness. Hence, we conclude that FD and λ serve as relevant parameters depicting the quality of coating surface at significance level of 0.05.